A study of demand forecasting in electronic manufacturing industry using time-series approach - Tan, Yi Hua (2014)
The study of the evaluation on the forecasting techniques applied in the manufacturing industry is known as very crucial part in the operation decision making for all electronic manufacturing service industry. The objectives of this research are to evaluate the demand forecasting method used by the manufacturing company, analyses the sale data of the company using several forecasting method and lastly propose the most suitable forecasting method to the manufacturing company. The forecasting method used in the analysis involved Time Series Forecasting Method. The forecasting method was assess by using forecast error measurement tool such as Mean Absolute Deviation (MAD), Mean Squared Error (MSE), Mean Absolute Percentage Error (MAPE) and Tracking Signal. These forecast error analyses were used to monitor the forecast result of various methods. The result of this study showed that trend projection was chosen as the most suitable forecasting method as it produces the most accurate result and least forecast error. Demand forecasting plays a critical role in every business especially in manufacturing industry. Most of the operations decisions in manufacturing industry are based on some kind of forecast for future demand. As a result, manufacturing company pay highly attention towards demand forecasting process and this study has devoted attention to this particular issue.